Detection of Cryptosporidium spp. in Diarrheic Immunocompetent Patients in Beni-Suef, Egypt: Insight into Epidemiology and Diagnosis - Abdel Gawad, Samah S. (Korean J Parasitol, 2018)
Cryptosporidium species is an important cause of gastrointestinal infections globally. This study aimed to shed light on its role in diarrheic immunocompetent patients in Beni-Suef, Egypt and to compare three diagnostic methods. Two hundred diarrheic patients, 37±16.8 year old, were enrolled. Stool samples were examined by light microscopy, using modified Ziehl-Neelsen stain (MZN) for Cryptosporidium spp. oocysts. Coproantigens were detected by sandwich ELISA. DNA molecular diagnosis was done by nested PCR. PCR yielded the highest detection rates (21.0%), compared to ELISA (12.5%) and MZN staining method (9.5%). The higher infection rates were in 20–40 year-old group, followed by 40–60 year-old. Association between epidemiologic factors was statistically not significant; positivity and gender, clinical manifestations, residence, source or water, or contact with animals. Cryptosporidiosis is an important enteric parasitic infection in Beni-Suef and PCR remains the gold standard for diagnosis.